Malawi Systematic Country Diagnostic : Breaking the Cycle of Low Growth and Slow Poverty Reduction - World Bank Group (World Bank, Washington, DC, 2019)
The Systematic Country Diagnostic (SCD) for Malawi provides the analytical foundation for country-level actions and investments to foster progress towards the World Bank Group (WBG) Twin Goals as well as the country’s national goals. The main purpose of the SCD is to identify the key challenges and opportunities that Malawi faces as it works towards eliminating extreme poverty and boosting shared prosperity in a sustainable manner. The systematic and evidence-based analysis from the SCD will serve to inform a new Country Partnership Framework and help the WBG, Government and external partners to prioritize and align their strategies towards achieving the twin goals. Over past decades, Malawi’s development progress has been negatively affected by shocks, both climate-related shocks, and domestic political and governance shocks, which have collectively contributed to a slow pace of poverty reduction. Very little progress has been made in reducing poverty in rural areas, where most Malawians live. Weak governance and entrenched political clientelism have been obstacles to policy reform and the development of the country. This SCD takes a holistic approach to identify the drivers of previous poor growth performances, drawing on the history of Malawi, and proposes a set of priority areas to promote durable and inclusive growth. The SCD is divided into six parts. The first part gives an overview of the country context, while the second part traces out the trends in economic growth. The third part analyses poverty and shared prosperity in Malawi and their main drivers. The fourth part provides the main diagnostics, identifying the key constraints and pathways for Malawi to achieve the twin goals. The fifth part outlines the preliminary hypotheses for achieving the twin goals, while part six indicates knowledge gaps and areas for further research.